Utilization of Moringa Leaf Flour as a Natural Immunostimulant to Increase the Growth of Gourami Fish (Osphronemus gouramy) - Indra Warman; Heti Novitasari; Bambang Putra Puspita; Gala Cristian (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to explore the potential of moringa leaf flour (Moringa oleifera) as a natural immunostimulant in feed that can optimally and sustainably improve the growth and resistance of gurame fish (Osphronemus gouramy). Methodology: The study was conducted at the Ratu Samban University Experimental Pond from July to September 2025 using a completely randomized block design (CRBD) with two factors. The first factor was the combination of commercial feed with moringa leaf flour, consisting of K1 (control), K2 (5%), K3 (10%), and K4 (15%). The second factor was the feeding duration, namely T1 (30 days) and T2 (60 days). Results: The addition of moringa leaf flour significantly affected the growth, feed efficiency, and proximate composition of gurame fish. The combination of moringa feed increased fish weight while decreasing the feed conversion ratio (FCR), with the best results observed at 30 days of feeding. Body protein content increased with moringa dosage, with the highest value at K4 (15%), while fat and ash content were relatively higher at K2 (5%). Overall, moringa bioactives improved nutritional quality, supported metabolism, and enhanced the immune response of fish. Findings: The optimal moringa dosage is 15% with a feeding period of 30 days. Novelty: This study confirms the dual function of moringa, not only as a source of nutrition but also as a natural immunostimulant for gurame fish. Originality: This study is the first to test moringa on gurame fish with varying doses and administration times. Conclusion: Moringa leaf powder has excellent potential as a natural feed ingredient to increase productivity and support sustainable aquaculture. Document type: empirical research article.